KOSMOLOGI DALAM SAMKHYA DARSANA - Luh Putu Cita Ardiyani; Desak Made Ayu Indri Safira (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2019)
Cosmology is the study of the universe. Cosmology is not only studied in science but also studied in Hinduism called Hindu Cosmology. In addition, in the view of Samkhya who is part of Sad Darsana also studies cosmology. Darśana is a part of Hindu writing which requires sharp intelligence, reasoning and feeling, because the main problem it discusses is the essence of overall Vedic understanding in the field of philosophy. Philosophy is a rational aspect of religion and is an integral part of religion. Other names or terms from the Darśana are; Mananaśāstra (philosophical thoughts or reflections), Vicaraśāstra (investigating philosophical truth), tarka (speculation), Śraddhā (belief or faith).